Peter Nikolaj Skougaard. Grundtvigs mathematiske ven - Nielsen, E. Brandt (Grundtvig-Studier, 1966)
Peter Nikolaj Skougaard and Grundtvig By E. Brandt Nielsen P. N. Skougaard was born in the island of Bornholm in the same year as Grundtvig and belonged to his circle of young fellow students. Grundtvig called him the only friend of his youth or his “mathematical friend”, Skougaard’s interests being mathematics and, especially, history. The common interest which brought them together was indeed history and dramatic art. History became their real sphere. The diary tells of Grundtvig’s struggle with historical matter and Skougaard’s energetic attempt to make him approach the study of the Arnemagnæan collection in a scholarly way. Skougaard is victorious, but only as regards the scholarly method and only in so far as Grundtvig leaves historical narrative in favour of linguistic and historical studies. In his way of getting to know the spiritual content of Norse poetry Grundtvig differed widely from his friend. Skougaard was a man of enlightenment, and Grundtvig’s existential interpretation of the Eddie poetry could only be very strange to him and double Dutch. The importance of Skougaard to the young Grundtvig is very great as indicated by numerous writings, printed as well as unprinted. Grundtvig compares him to people like Snorre, Schiønning, Gräter, and Nyerup, and he draws a parallel to the influence which he received from Henrik Steffens. Although they probably did not see each other after their meeting in the island of Langeland in 1807, and although he often changed his opinion of other people, Grundtvig’s opinion of P. N. Skougaard remained remarkably unaltered from the early poetry, the diaries, to Kirke-Speil, the work of his old age. Skougaard became Grundtvig’s scholarly conscience and his personal adviser in the “Egeløkke”- crisis— indeed, Grundtvig does not hesitate to describe his encounter with the young Skougaard in 1801 as decided by fate itself. As human beings the two friends could hardly have been less alike, and Grundtvig points to the fact himself. Skougaard’s life became something of a tragedy, determined more by inward tendencies than by outward circumstances. He let himself be defeated by adversity— a young historical writer he was subjected to life censorship according to the printing ordinance of 1799; he did not, like Grundtvig, eventually obtain exemption— Grundtvig, on the other hand, always made external adversity become a challenge and an incitement to still greater achievements. The purely psychological relationship between the two young friends may seem rather puzzling. For instance, revising the article on the investigation of antiquity for Danne-Virke Grundtvig tries to objectify his relations with Skougaard, just as he leaves out the highly personal words about him in the final version of the poem “Strandbakken ved Egeløkke”— an attempt, in other words, at an objective limitation of Skougaard’s influence; but elsewhere, not least in the foot-note to the preface of Nordens Mytologi 1808, the expression of personal feelings is given free scope. But, as the scholar who chooses, first and foremost, the literature for Grundtvig to take with him to “Egeløkke” and who energetically forces him away from his aesthetic and historical mistake: the historical narrative— and by his strong and original personality, Skougaard acquired an importance for Grundtvig which was unique,— it was so great that in my opinion one might well ask how Grundtvig would have developed, had not Skougaard influenced his scholarly work and personal life. For this reason the name of Peter Nikolaj Skougaard should be remembered and rehabilitated. He deserves it.